Wilhelm Wundt through the Eyes of a Student from Lithuania: Records in the Diary of Vytautas Civinskis Related to Psychology Lectures at Leipzig in 1905 - Almonaitienė, Junona S.; Girininkaitė, Veronika (Psichologija, 2022)
The article addresses aspects of the connections between Wilhelm Wundt and Lithuania. It is introduced by briefly mentioning facts known from previous research about Lithuanians who studied at Wundt’s Institute of Experimental Psychology at Leipzig, and those who chose Wundt’s work as the object of their research. In the main part of the article, for the first time, excerpts from a manuscript with Lithuanian student’s impressions about Wundt’s psychology lectures he attended are published in Lithuanian and in original multilingual text. It was written by Vytautas Civinskis (Polish Witold Cywiński, 1887–1910), the student of agricultural sciences at Leipzig University, in his Diary in 1905. Although small in volume and written by a very young person, these recordings are interesting as an authentic testimony. According to the available data, this is the only surviving archival document of such kind written by a student from Lithuania. From the document, it is possible to deduce how the student evaluated Wundt as a lecturer, what were the content and form of his lectures, as well as the physical, social and intellectual environment at Leipzig, and what opportunities all that provided for students. The mentioned aspects are discussed in the comments of the archival materials. It is concluded that bringing to awareness the fact of existence of the student’s Diary entries related to Wundt’s lectures complements the Lithuanian psychology history quite significantly, and their content reveals Wundt’s attention to the philosophical basis of experimental psychology, psychophysiology, the details of several experiments he demonstrated.